Product Family Formation for Reconfigurable Manufacturing using a Bi-criterion Evolutionary Algorithm - Pattanaik, Laxmi Narayan; Kumar, Vikas (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
The aim of this paper is to group products into several product families as required during reconfigurable manufacturing considering their operation sequences and demands. A reconfigurable manufacturing system (RMS) is designed for rapid adjustment of production capacity and functionality in response to new market conditions and new process technology. Products are grouped into families and each of which requires a distinct and optimum system configuration. The system is reconfigured in order to produce another family and so forth. The effectiveness of an RMS hence depends on the formation of the set of product families. Methodology for grouping products into families, considering the requirements of RMSs, is a recent research issue which is addressed in this paper. The two most important characteristics of RMS that enables it to cope with variations in capacity and functionality are considered during product family formation. A bi-criterion evolutionary genetic algorithm is used to identify the Pareto optimal solutions representing the product families for the RMS.